Linking in vitro lipolysis and microsomal metabolism for the quantitative prediction of oral bioavailability of BCS II drugs administered in lipidic formulations - Benito-Gallo, Paloma; Marlow, Maria; Zann, Vanessa; Scholes, Peter; Gershkovich, Pavel (American Chemical Society, 2016)
Lipidic formulations (LFs) are increasingly utilized for the delivery of drugs that belong to class II of the Biopharmaceutics Classification System (BCS). The current work proposes, for the first time, the combination of in vitro lipolysis and microsomal metabolism studies for the quantitative prediction of human oral bioavailability of BCS II drugs administered in LFs. Marinol® and Neoral® were selected as model LFs and their observed oral bioavailabilities (Fobserved) obtained from published clinical studies in humans. Two separate lipolysis buffers, differing in the level of surfactant concentrations, were used for digestion of the LFs. The predicted fraction absorbed (Fabs) was calculated by measuring the drug concentration in the micellar phase after completion of the lipolysis process. To determine first-pass metabolism (Fg∙Fh), drug depletion studies with human microsomes were performed. Clearance values were determined by applying the “in vitro half-life approach”. The estimated Fabs and Fg∙Fh values were combined for the calculation of the predicted oral bioavailability (Fpredicted). Results showed that there was a strong correlation between Fobserved and Fpredicted values only when Fabs was calculated using a buffer with surfactant concentrations closer to physiological conditions. The general accuracy of the predicted values suggests that the novel in vitro lipolysis/metabolism approach could quantitatively predict the oral bioavailability of lipophilic drugs administered in LFs.